2016
DOI: 10.1177/1470320316655037
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum levels of AngII, KLK1, and ACE/KLK1 polymorphisms with acute myocardial infarction induced by coronary artery stenosis

Abstract: Introduction:The study aims to confirm the association of acute myocardial infarction (AMI) with serum angiotensin II (AngII), kallikrein1 (KLK1), and ACE/KLK1 polymorphisms.Materials and methods:Serum AngII/KLK1 levels and ACE and KLK1 genotypes were determined in 208 patients with AMI and 216 normal controls. Binary logistic regression was used for data analysis.Results:The differences in serum AngII levels were statistically significant between the groups. After adjusting for potential confounding factors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…The diagnosis of hypertension and diabetes mellitus was performed according to World Health Organization criteria A smoking habit was defined as a daily intake of >10 cigarettes continuing for more than 1 year. The other criteria are consistent with a previous study 4 . The fasting blood samples tested for routine blood, lipid profiles and coagulation tests were routinely performed in the hospital laboratory.…”
Section: Methodssupporting
confidence: 92%
See 2 more Smart Citations
“…The diagnosis of hypertension and diabetes mellitus was performed according to World Health Organization criteria A smoking habit was defined as a daily intake of >10 cigarettes continuing for more than 1 year. The other criteria are consistent with a previous study 4 . The fasting blood samples tested for routine blood, lipid profiles and coagulation tests were routinely performed in the hospital laboratory.…”
Section: Methodssupporting
confidence: 92%
“…A human angiotensin I-converting enzyme (ACE) gene insertion/deletion (I/D) polymorphism, due to I/D of a 287-base pair element in intron 16 of this gene, is associated with the development of AMI by modifying ACE activity and contributing to enhanced plaque vulnerability, ulceration and thrombosis 2,3 . Our recent case-control study has also demonstrated that the ACE DD genotype is an independent risk factor for STEMI 4 .…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…In this line, a human angiotensin I-converting enzyme (ACE) gene insertion/deletion (I/D) polymorphism, located on chromosome 17q23, is associated with CVD [5,6]. The ACE I/D polymorphism consists in the presence (insertion, I) or absence (deletion, D) of a 287 base pair fragment in intron 16 of ACE gene [7].…”
Section: Introductionmentioning
confidence: 99%
“…The ACE gene produces the protein ACE, which converts angiotensin (AngI) into angiotensin II (AngII), a potent vasoactive peptide that leads to effects mainly hypertensive, highlighting its role in the physiology of blood vessels and inflammation [5,8]. Indeed, higher plasma levels of ACE have been reported when the D allele was present [5], accordingly, the ACE DD genotype has been established as an independent risk factor of CVD and hypertension [6,9]. Similarly, a recent meta-analysis [10] has shown a higher risk of hypertrophic cardiomyopathy in the DD genotype than in the II genotype; therefore, a protective effect against CVD risk can be attributed to the II genotype.…”
Section: Introductionmentioning
confidence: 99%